Influence of Particle Size of Enogen Feed High Amylase and Conventional Yellow Dent Corn on Finishing Pig Performance, Carcass Characteristics, and Stomach Ulceration - H. R. Williams; M. D. Tokach; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey; S. S. Dritz; V. Shivanna; C. B. Paulk; H. I. Calderón (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 323 pigs (DNA 241 × 600; initially 109.8 lb) were used in an 83-d growth trial to evaluate the influence of particle size of Enogen Feed corn (Enogen, Syngenta Seeds, LLC, Downers Grove, IL) and conventional yellow dent corn on finishing pig performance. Pigs were randomly assigned to pens (9 pigs per pen) and pens were allotted by weight to 1 of 6 dietary treatments in a randomized complete block design with 6 pens per treatment. Treatments were arranged in a 2 × 3 factorial with main effects of corn source (Enogen Feed corn or conventional yellow dent) and 3 ground corn particle sizes (300, 600, or 900 microns). Overall, from d 0 to 83, there were no differences among corn sources observed for average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G). As particle size of the diet decreased from 900 to 300 microns, ADG increased (linear, P = 0.018). Overall F/G improved (linear, P = 0.021) as corn particle size was decreased. In summary, reducing the particle size of the diet improves feed efficiency with no major differences between corn sources for overall pig performance.
Keywords: corn; high amylase; nursery pigs; particle size